2017
DOI: 10.1093/mnras/stx815
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the multifrequency pulse profiles of PSRs B0329+54 and B1642–03 in an inverse Compton scattering model

Abstract: The emission geometries, e.g. the emission region height, the beam shape, and radiusto-frequency mapping, are important predictions of pulsar radiation model. The multiband radio observations carry such valuable information. In this paper, we study two bright pulsars, (PSRs B0329+54 and B1642−03) and observe them in high frequency (2.5 GHz, 5 GHz, and 8 GHz). The newly acquired data together with historical archive provide an atlas of multi-frequency profiles spanning from 100 MHz to 10 GHz. We study the frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Here, P is three times of period of J0815+0939. Shang et al 2017Shang et al , 2021 for details), and find that the separations of the four components are 38.29 ± 0.66 ms, 69.88 ± 1.60 ms and 41.16 ± 1.15 ms at the 1250 MHz band, respectively. This is different from that in previous observation of 400 MHz.…”
Section: The Mean Pulse Profilesmentioning
confidence: 98%
“…Here, P is three times of period of J0815+0939. Shang et al 2017Shang et al , 2021 for details), and find that the separations of the four components are 38.29 ± 0.66 ms, 69.88 ± 1.60 ms and 41.16 ± 1.15 ms at the 1250 MHz band, respectively. This is different from that in previous observation of 400 MHz.…”
Section: The Mean Pulse Profilesmentioning
confidence: 98%
“…where ψ is the observed position angle, the impact angle & Manchester 1988;Zhang et al 2007;Shang et al 2017), and f is the longitude, defined to be zero on the magnetic meridian. Here ψ 0 and f 0 are offset from the position angle and phase, respectively.…”
Section: The Average Pulse Profilementioning
confidence: 99%
“…A pulsar is known for its highly periodic pulse emission. The shape of its mean pulse profile, which is folded by the single pulse, is usually very stable (Helfand et al 1975;Kramer et al 1994;Kramer 1994;Qiao et al 2001;Shang et al 2017Shang et al , 2020Shang et al , 2021. However, it is found that the single pulses, which represent the detailed emission process, are different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Then the radiation beamwidth is ρ beam ≈ 7°.0 in this case, which is consistent with the observations. Later, we combine Equation (33) with r r r sin e 2 e 2 q q = » (for a small θ) and a frequency of curvature radiation It can be estimated from Figure 5 of Shang et al (2017) that r ≈ 155 km is where the radiation with a frequency of 2 GHz is generated. Using the data from PSR B0329+54 mentioned above, we find that the Lorentz factors are γ d ≈ 441 (this is consistent with the observation).…”
Section: Pure Dipole Fieldmentioning
confidence: 99%